Assessing the Adherence to Ethical Principles of Accuracy and Fairness by Journalists in Rivers State: A Cursory Look at RHYTHM 93.7 FM - Ibituru Iwowari Pepple (Darul Yasin Al Sys, 2026)
Journalism codes of ethics provide normative principles to guide media practice, requiring journalists to act ethically, independently, fairly, and respectfully while reporting verifiable facts. However, the principles of accuracy and fairness are among the most frequently violated, leading to omission of crucial details and dissemination of misinformation that may trigger unnecessary public anxiety. This study examines the level of adherence to professional ethics, particularly the principles of accuracy and fairness—among journalists in Rivers State, Nigeria, with specific attention to Rhythm 93.7 FM Port Harcourt. Anchored in Absolutist and Social Responsibility theories, the research adopts a mixed-method design combining survey and in-depth interviews. The population comprises 500 registered journalists in Rivers State, approached using the census principle, with questionnaire schedules and in-depth interview guides as primary instruments for data collection. The findings indicate that a majority of journalists in Rivers State do not consistently adhere to the principles of accuracy and fairness in their reportage, partly due to pressures of strict deadlines that limit opportunities for thorough data verification. The study concludes that, although absolute accuracy may be difficult to attain under time constraints, media organisations must institute stronger editorial control mechanisms and support systems to enhance ethical compliance. It recommends that media organisations regularly organise training programmes, seminars, and workshops to reinforce journalists’ commitment to professional ethics, thereby strengthening the media’s responsibility to the public and improving the quality of news reporting.